The Impacts of Parenting Styles on the Symptoms of Conduct Disorder among High School Students in Pakdasht - A. Garmsiri Mahvar; S. Shokrzadeh, Ph.D. (خانواده و پژوهش, 2020)
This study sought to investigate the impacts of parenting styles on the symptoms of conduct disorder among high school students. In this descriptive research the statistical population was comprised of all parents of male high school students in Pakdasht in school year 2017-18. Purposive sampling was utilized and after diagnosing students with conduct disorder via the Child Symptom Inventory (CSI-4, Gadow & Sprafkin, 1994) and DSM-IV checklist (2013), a sample of 72 parents was selected. The sample was administered the Baumrind Parenting Style Inventory (PSI, 1991). Pearson correlation coefficient and multivariate regression analysis were used to analyze the data. Results demonstrated that there was a significant, positive relationship between authoritarian and permissive parenting styles and symptoms of conduct disorder. However, there was a significant, negative association between authoritative parenting style and symptoms of conduct disorder. In contrast to permissive parenting style, authoritarian and authoritative styles could account for a considerable amount of variance in the symptoms of conduct disorder. Accordingly, it can be stated that parenting styles are among the most determining factors affecting childhood growth and development and play a vital role in children’s healthy behavior.